Caracterização física, química e biológica da água na sub-bacia B1, do Rio Cocó, Fortaleza-CE, com ênfase nos aspectos da poluição ao longo de um ciclo climático - Lima, Isabelly Silva (2012)
This study aimed to evaluate the physical, chemical, biological, and the occurrence of both the acute toxicity and the diversity and quantity of phytoplankton biomass, along a climatic cycle, on sub-basin B1, a member of the Cocó River basin, Fortaleza - CE. The sampling occurred monthly on fourteen collecting points in the period of September 2010 to April 2011, in the exception of February 2011 that could not run it. With the parameters analyzed, temperature, transparency, pH, turbidity, true color, conductivity electrical, solids and fractions, calcium, magnesium, dissolved oxygen, chlorides, BOD5, QOD, phosphorus and fractions, sulfate, sulfide, total iron, Chlorophyll "a", total ammonia, nitrite, nitrate, organic nitrogen, total kjeldahl nitrogen, thermotolerant coliforms, Escherichia coli, acute toxicity, identification and enumeration of phytoplankton, have indicated variation in space due to different human impacts suffered. All the sub-basin B1 is found eutrophic, mainly due to the release of organic matter and nutrients, especially phosphorus. Although the monitored period to present court wintry atypical, with above the average rainfall, it was not enough to cause the dilution and possible legal framework, mainly at the oil and grease, total phosphorus and thermotolerant coliforms. In most of the monitoring, the sub-basin B1 showed signs of toxicity; only in the month of April was observed acute toxicity, which may be due to the rainfall some days before collection. With respect to phytoplanktonic diversity during the dry season to occurred the presence of 58 taxon and 7 classes and at court wintry, diversity increases to taxon 65 and 10 classes. The classes who lead both periods are: Chlorophyceae e Cyanobacteria. However, Aphanocapsa spp is the dominant class in both periods, at all points monitored, with values above the limit set by law, which is very worrying, because it is a potentially toxic species.